Theoretical evaluation of pressure and volumetric modules in inorganic metals silicon, selenium, tellurium, germanium - Kazhikenova, S.Sh. (Publishing House of the KarSU named after E.A.Buketov, 2014)
Based on the double-structured model of the melt with the cluster and atomic components with the involvement of the two mechanisms of thermal clusters’ decay, experimental and theoretical results on the structural states of the melts are interpreted. A possible explanation of the proposed two-structural model is in the neglect of the components of electron-ion interaction of the higher order than the second one. More over the inadequacy of pseudo-potential modification by means of the correction to the Hartee energy leads to the correct result only in the long-wave limit also. The given correlations allow us to calculate the compressibility of the melts. The theoretical calculated polyterms of the compressibility to selenium, tellurium, germanium and silicon are shown.
Keywords: Cluster structure; melt; polyterms of compressibility; semiconductor; structural factor; function of radial distribution